2020
DOI: 10.1007/s42452-020-1990-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified QuEChERS method to determine multiclass multipesticide residues in apple, banana and guava using GC–MS and LC–MS/MS and its application in real sample analysis

Abstract: A modified QuEChERS method was developed for the determination of 64 pesticides in apple, guava andbanana using GC-MS and LC-MS/MS. Out of sixty-four pesticides, 39 (32 insecticides + 7 herbicides) were analysed by GC-MS and others were analysed in LC-MS/MS. The efficiency of methanol, ethyl-acetate and acetonitrile as extracting solvents were checked. Among these, acetonitrile gave the highest recovery. d-SPE clean-up was done for apple and guava using PSA, whereas PSA + GCB was used for banana to remove hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The removal of color for both sorbents has been previously shown in different studies using dispersive clean-up. 16,35,36 To further explore the clean-up effect of different sorbent compositions, an evaluation of the co-extractive efficiency removal was made in terms of the chromatographic background by comparing the TICs of the sample extract before and aer mSPE clean-up using the formula in paragraph 2.4. The TICs obtained from GC-MS scan are shown in Fig.…”
Section: Analytical Instrumentmentioning
confidence: 99%
“…The removal of color for both sorbents has been previously shown in different studies using dispersive clean-up. 16,35,36 To further explore the clean-up effect of different sorbent compositions, an evaluation of the co-extractive efficiency removal was made in terms of the chromatographic background by comparing the TICs of the sample extract before and aer mSPE clean-up using the formula in paragraph 2.4. The TICs obtained from GC-MS scan are shown in Fig.…”
Section: Analytical Instrumentmentioning
confidence: 99%
“…The rapid detection of pesticide residues in fruits and vegetables through UPLC-MS/MS coupled with QuEChERS has been intensively researched and has revealed that adding a certain amount of water to vegetables and fruits with low water content improves the extraction effects [28]. Considering the high sweetness and viscosity of mixed fruit purees, adding a certain amount of water can increase the recovery rate.…”
Section: Optimization Of Water Additionmentioning
confidence: 99%
“…1) 38,39 as well as other 8 pesticides spiked in cabbage samples prepared by the QuEChERS method. 40,41 The high amount of these target pesticides accumulated in cabbage can be associated with both carcinogenic and noncarcinogenic health risks, particularly for children. 42 Thus, the investigation of these pesticide residuals becomes crucial.…”
Section: Introductionmentioning
confidence: 99%